2022
DOI: 10.3389/fendo.2022.985588
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prevalence, knowledge of polycystic ovary syndrome and health-related practices among women in klang valley: A cross-sectional survey

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is a common metabolic and reproductive disorder affecting women of childbearing age. Its symptoms associated with androgen excess and menstrual abnormalities have great impact on the quality of life in women with PCOS. Data on the knowledge of PCOS and health-related practices among Malaysian women is scarce. This study aimed to determine the prevalence, knowledge and health-related practices of PCOS among women in Klang Valley, Malaysia.MethodA descriptive cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Thus, there is a lack of understanding regarding PCOS due to cultural taboos and stigmas around discussing menstruation or female reproductive health concerns in an open manner. More similar kind of study also found that most of the participants had poor knowledge and health-related practices toward PCOS [22,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a lack of understanding regarding PCOS due to cultural taboos and stigmas around discussing menstruation or female reproductive health concerns in an open manner. More similar kind of study also found that most of the participants had poor knowledge and health-related practices toward PCOS [22,[42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…According to estimates, 13% of fertile Egyptian women and 37.5% of secondary infertile women have PCOS (Ibrahim et al, 2023). Research has indicated a growing trend in PCOS prevalence since the late 1900s (Deswal, 2020;Goh et al, 2022).…”
Section: ) Significancementioning
confidence: 99%
“…Another study conducted in 2021 aimed to estimate knowledge and practice towards weight loss among women with PCOS, in which a descriptive analysis was used and search engines such as Google Scholar and PubMed, it was also found that there is insufficient knowledge about PCOS and its complications [13].…”
Section: N E E Malik Et Almentioning
confidence: 99%